2022
DOI: 10.3390/ma15145061
|View full text |Cite
|
Sign up to set email alerts
|

Selected Physical and Spectroscopic Properties of TPS Moldings Enriched with Durum Wheat Bran

Abstract: The impact of the amount of durum wheat bran additive used on the selected structural, mechanical, and spectroscopic properties of thermoplastic starch moldings was examined in this study. Bran was added to corn starch from 10 to 60% by weight in the blends. Four temperature settings were used for the high-pressure injection: 120, 140, 160, and 180 °C. The highest value of elongation at break (8.53%) was observed for moldings containing 60% bran. Moreover, for these moldings, the tensile strength and flexural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…WB is the waste material in flour production. It consists mainly of lignocellulosic materials including cellulose, lignin, hemicellulose, and also phytic acid, oligosaccharides, non-starch polysaccharides, as well as fats and proteins [41][42][43]. The main goal of this paper was to investigate the relationship between the properties of polymer compositions based on PBS and the content and type of fillers of plant origin, OP and WB.…”
Section: Introductionmentioning
confidence: 99%
“…WB is the waste material in flour production. It consists mainly of lignocellulosic materials including cellulose, lignin, hemicellulose, and also phytic acid, oligosaccharides, non-starch polysaccharides, as well as fats and proteins [41][42][43]. The main goal of this paper was to investigate the relationship between the properties of polymer compositions based on PBS and the content and type of fillers of plant origin, OP and WB.…”
Section: Introductionmentioning
confidence: 99%
“…Dominici et al, also found that the bran % content in wholegrain flours of bread wheat may affect the tensile properties of thermoplastics [12]. Combrzy ński et al observed that the amount of durum wheat bran additive used, as well as the temperature of high-pressure injection molding, both had a significant impact on the structure and mechanical properties of the TPS moldings subjected to mechanical strength testing [13]. Robin and coauthors also found that bran concentration influenced the glass transition temperature, melting temperature and sorption isotherm of the unprocessed wheat flour, that might contribute to the modulation of the expansion properties of a bran-containing starchy foam [14].…”
Section: Introductionmentioning
confidence: 99%